Dequalinium-Derived Nanoconstructs: A Promising Vehicle for Mitochondrial Targeting - Pawar, Abhishek; Korake, Swati; Gajbhiye, Kavita R. (Current Drug Delivery, 2021)
The cell's power house, mitochondrion, is a vital organelle for drug targeting in the treatment of many diseases due to its fundamental duties and function related to cell proliferation and death. The mitochondrial membrane comprises bilayer artifact and poses extremely negative potential, creating hurdles for therapeutic molecules in reaching mitochondria. To accomplish mitochondrial targeting, the scientific community has explored diverse pharmaceutical formulations like liposomes, polymeric nanoparticles (NPs), and inorganic NPs. However, the game changing technology was a modification of these carriers by mitochondriotropic moiety, dequalinium chloride (DQA) or delivering the chemotherapeutics by DQAsomes. The DQA represents a distinctive mitochondriotropic delocalized cation that displays their selectivity towards accumulation in mitochondria of carcinoma cells. Attributed to this characteristics, DQAsomes have been formulated using DQA and explored for successful mitochondrial targeting of bioactives. In this review, it is discussed the effectiveness of DQA nanocarriers which efficiently and selectively transmit the cytotoxic drug to the tumor cell. The DQA based nanoformulations have evidently displayed augmented pharmacological and therapeutic outcomes than their counterparts both in vitro and in vivo. Thus, DQAsomes symbolizes an ideal carrier with excellent potential as mitochondrial targeting agent.
Keywords: Dequalinium chloride